1999
DOI: 10.1046/j.1365-2311.1999.00169.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in species composition of dung beetle assemblages in southern Ireland

Abstract: 1. This study attempts to identify the main community characteristics that contribute to variability in dung beetle assemblage composition and structure across a range of spatial and temporal scales.2. Dung beetle assemblages (Aphodius, Sphaeridium, and Geotrupes species) were monitored by dung-baited pitfall trapping at 10-day intervals during the seasonally active period at eleven sites in southern Ireland. Three of the sites were monitored over at least 2 years between 1991 and 1996.3. Although the species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 22 publications
2
26
0
1
Order By: Relevance
“…The main temporal turnover occurs between September and October in central and northern Europe (Wassmer, 1994;Finn et al, 1999). In Tunisia, Aphodiinae-dwellers (Ad) showed a temporal constancy from November to May, and St from March till October.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The main temporal turnover occurs between September and October in central and northern Europe (Wassmer, 1994;Finn et al, 1999). In Tunisia, Aphodiinae-dwellers (Ad) showed a temporal constancy from November to May, and St from March till October.…”
Section: Discussionmentioning
confidence: 99%
“…In Northern Europe, communities of coprophagous beetles are dominated by Aphodiidae (Finn et al, 1999). Wassmer (1994) showed that the temporal dimension is an important factor structuring communities of dungbeetles in Central Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some species of other beetle families such as Hydrophilidae and Staphylinidae are also commonly found in dung and could be considered dung beetles as well (Hanski, Cambefort 1991). Nevertheless, they are not coprophagous during their entire life cycle (Finn et al 1999), and they do not contribute to lateral or vertical dung transport which was one of the major research goals of our study. Therefore, dung beetles were strictly defined as the coprophagous species in the Geotrupidae and Scarabaeidae families.…”
Section: Taxonomic Coverage and Dung Beetle Classificationmentioning
confidence: 99%
“…A commonly used sampling method for this approach is pitfall trapping (e.g., Work et al 2002). Many studies using pitfall traps showed that beetle species occurrences change throughout the year or at least show clear seasonal abundance patterns (e.g., French & Elliott 1999;Finn et al 2001;JayRobert et al 2008). These results support the necessity of ABSTRACT.…”
mentioning
confidence: 99%